A qualitative study on strategies to overcome demotivation, burnout, and boredom in weight loss among women in reproductive age - Fajriati Ramadhini Nur Mileniati; Fajar Ari Nugroho; Fuadiyah Nila Kurniasari (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
The rising prevalence of obesity among adults, particularly women, highlights the need for effective weight management strategies. While previous studies have explored weight loss adherence, limited research has focused on the psychological strategies that reproductive-age women use to maintain their motivation in diet and physical activity. This qualitative study was conducted from September until October 2024 and employed a narrative approach, involving in-depth interviews with six key informants in Bandung City who had experienced or participated in a weight loss program. Additional informants were also included to support the triangulation method. Data were thematically analyzed using NVivo 12 for coding and Microsoft Excel for data tabulation. The study revealed five strategies for overcoming demotivation, burnout, and boredom. (1) Reflecting on Achievements, (2) taking a break for a while, (3) embracing the flexibility of diet and physical activity, (4) remembering the motivation they started to lose weight, and (5) adjusting the intensity of exercise. In conclusion, reflecting on achievement could be a strategy to overcome demotivation, burnout, or boredom during the weight loss journey. Nevertheless, the effectiveness of these strategies depends on individual characteristics. Personalized approaches to weight loss programs can be integrated into community-based initiatives and healthcare practices to enhance long-term adherence through group support, educational campaigns, coaching in healthier eating practices, and stress management.